EFEKTIVITAS METODE MONTESSORI DALAM MENGATASI KESULITAN MEMBACA PERMULAAN SISWA KELAS I UPT SPF SD NEGERI BAWAKARAENG I KOTA MAKASSAR - Nur Abidah Idrus; Yusnadi Yusnadi; Hajirah Hajirah (Universitas Negeri Makassar, 2025)
This research aimed to determine the effectiveness of the Montessori method in addressing beginning reading difficulties among first-grade students at UPT SPF SD Negeri Bawakaraeng I, Makassar City, utilizing a quantitative approach with a pre xperimental research, specifically One Group Pretest-Postest Design, involving 80 students subject. Data were collected via a beginning reading ability test and and observation sheets and analyzed by using descriptive statistic and the nonparametric Wilcoxon signed-rank test to assess the significance of effectiveness. The findings indicates a clear increase in the mean score for beginning reading ability, rising from 59,80 in the pretest to 72,26 in the posttest. The implementation of the Montessori method also improved to the very good category. Furthermore, the inferential statistical analysis yielded a p-value of <0,001(less than α=0,05), demonstrating a significant difference in students’ beginning reading ability post-intervention. The study conclude that the Montessori method is effective in improving beginning reading ability and overcoming reading difficulties.